Penanganan Stunting Kampung Lalang: Sosialisasi Serta Pembagian Vitamin Oleh Kelompok Kukerta Universitas Riau - Anastasya Carolista Pakpahan; Artika Dewi Sitanggang; Benget Hasiholan; M Aldrian Mustafarsyach; Fadzil Aulia Rahman; Nelsi Ramadhani; Aulia Merlin Bestari; Rayu Zatdra (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2023)
The Real Working Lecture (KKN) is a vehicle for the application and development of knowledge, which is carried out off campus in certain time, work mechanism, and requirements. KKN implemented by universities is an effort to increase the content and weight of education for students and to get greater added value to higher education. Through community service activities in Lalang Village, there will be synergy between universities and the community. The purpose of this KKN acticity is to provide an understanding to the local community about the importance of health for young generation, specifically for their babies. Frequently, stunting become a massive issues for babies in this village. The service is carried out through educational workshops, seminars, teaching, and discussions. The result of this dedication provide an overview of how importance for a mother and their kids to mantaian what they eat and how to have a healhty live due to stunting issues.